Genome-wide mutational analysis of Chikungunya strains from 2016 to 2017 outbreak of central India: An attempt to elucidate the immunological basis for outbreak. Issue 11 (November 2022) - Gupta, Sudheer; Yadav, Ashvini; Stubbs, Sam; Frost, Simon; Ansari, Kudsia; Nema, Ram Kumar; Nema, Shashwati; Biswas, Debasis
Abstract: Chikungunya re-emerged in India in 2016–2017, as the first major outbreak since 2006. In our previous study, we undertook partial E1 gene sequencing and phylogenetic/mutational analysis of strains from the 2016–2017 outbreak of Chikungunya in central India and reported important mutations associated with the outbreak. This study was performed to validate the previous findings and to identify key mutations that had emerged throughout the entire genome of Chikungunya virus that could be driving the enormity of this outbreak. The phylogenetic analysis revealed the closeness of our isolates with ECSA genotype, specifically with the Singapore 2015 strain. We found 2 mutations in C and E2 genes, which were present in our isolates but were non-existent during the period of 2010–2016. Furthermore, re-emergence of Arg amino acid in place of stop codon in nsP3 gene and Thr at E2:312 positions was observed after 2011. We also used computational tools to assess the effect of the identified mutations on the T cell and B cell epitopes that could influence the protective immune response against this infection. Abstract : Chikungunya; Phylogenetics; Outbreak; Genome sequencing; Nanopore.